What is CPD?. (2nd February 2022) - Bradbury, Aaron
Abstract : We know that high quality learning and Continual Professional Development (CPD) for early years professionals can often feel like finding a needle in a haystack. Here I explain what CPD is, the different forms it can take place in and why it is important.